Soil Quality Along a Distances Gradient from Shorelines in Samas Coastal Sandy Land, Bantul, Yogyakarta: Kualitas Tanah pada Jarak Garis Pantai di Lahan Pertanian Pasir Pantai Samas, Bantul, Yogyakarta - Sepia Intan Cahyani Putri, Theresia; Herlambang, Susila (Universitas Pembangunan Nasional Veteran Yogyakarta, 2025)
Samas coastal sandy land is characterized as a marginal agricultural area, approximately 4 km from the shoreline. This study was conducted with three primary objectives: to evaluate its soil characteristics, to calculate its soil quality index (SQI), and to examine the limiting factors for soil quality. This study used a purposive survey method, sampling points were selected at varying distances from the coastline. Soil quality parameters analyzed included root density, weight density, porosity, clay content, C-organic, total N, available N/P/K, pH, and microbial counts (CFU/g). Soil quality was evaluated based on the criteria by Mausbach & Seybold (1998) and scoring function from Karlen et al. (1996), both of which were adapted to local conditions. The results showed that the 1 km from the coastline had the highest sand content (62.041%) but the lowest microbial counts (670×10³ CFU/g), while soils 4 km inland showed the lowest sand content (19.819%) and highest C-organic (1.297%), total N (0.392%), C/N ratio (3.309), and microbial activity (1910×10³ CFU/g). Available N, P, and K were consistently high across all sites. The soil quality index (SQI) increased with distance from the coast, transitioning from